Serology testing in the COVID-19 pandemic response - Peeling, Rosanna W (Lancet Infect Dis, 2020)
The collapse of global cooperation and a failure of international solidarity have led to many low-income and middle-income countries being denied access to molecular diagnostics in the COVID-19 pandemic response. Yet the scarcity of knowledge on the dynamics of the immune response to infection has led to hesitation on recommending the use of rapid immunodiagnostic tests, even though rapid serology tests are commercially available and scalable. On the basis of our knowledge and understanding of viral infectivity and host response, we urge countries without the capacity to do molecular testing at scale to research the use of serology tests to triage symptomatic patients in community settings, to test contacts of confirmed cases, and in situational analysis and surveillance. The WHO R&D Blue Print expert group identified eight priorities for research and development, of which the highest is to mobilise research on rapid point-of-care diagnostics for use at the community level. This research should inform control programmes of the required performance and utility of rapid serology tests, which, when applied specifically for appropriate public health measures to then be put in place, can make a huge difference.